Malicious Dwarfs, Fair Nymphs, Heroic Gods. Application and Transformation of Germanic Mythology in Richard Wagner’s libretto «The Rhinegold» (Studia theodisca, 2012)
According to Joachim Heinzle, the Nibelungensage represents the «most German among all German issues». The following essay seeks to analyze in how far the German composer Richard Wagner resorts either to a more traditional or to a more innovative representation of the Germanic influences in his libretto The Rhinegold, which is the opening part of his operatic tetralogy The Ring of the Nibelungen. Moving from an epistemological basis, the libretto will be examined with a special focus on how Wagner applies and transforms Germanic mythology in terms of the characters and of deictic references.